Acute Kidney Injury and Fluid Overload in Pediatric Extracorporeal Cardio-Pulmonary Resuscitation: A Multicenter Retrospective Cohort Study. Issue 7 (12th October 2022) - Gist, Katja M.; Misfeldt, Andrew; Sahay, Rashmi D.; Gorga, Stephen M.; Askenazi, David J.; Bridges, Brian C.; Paden, Matthew L.; Zappitelli, Michael; Gien, Jason; Basu, Rajit K.; Jetton, Jennifer G.; Murphy, Heidi J.; et al.
Abstract : Acute kidney injury (AKI) and fluid overload (FO) are common complications of extracorporeal membrane oxygenation (ECMO). The purpose of this study was to characterize AKI and FO in children receiving extracorporeal cardiopulmonary resuscitation (eCPR). We performed a multicenter retrospective study of children who received eCPR. AKI was assessed during ECMO and FO defined as <10% [FO−] vs. ≥10% [FO+] evaluated at ECMO initiation and discontinuation. A composite exposure, defined by a four-group discrete phenotypic classification [FO−/AKI−, FO−/AKI+, FO+/AKI−, FO+/AKI+] was also evaluated. Primary outcome was mortality and hospital length of stay (LOS) among survivors. 131 patients (median age 29 days (IQR:9, 242 days); 51% men and 82% with underlying cardiac disease) were included. 45.8% survived hospital discharge. FO+ at ECMO discontinuation, but not AKI was associated with mortality [aOR=2.3; 95% CI: 1.07–4.91]. LOS for FO+ patients was twice as long as FO− patients, irrespective of AKI status [(FO+/AKI+ (60 days; IQR: 49-83) vs. FO−/AKI+ (30 days, IQR: 19–48 days); P = 0.01]. FO+ at ECMO initiation and discontinuation was associated with an adjusted 66% and 50% longer length of stay respectively. Prospective studies that target timing and strategy of fluid management, including its removal in children receiving ECPR are greatly needed.